The Maré Museum: an integrated project of community development (Cadernos de Sociomuseologia, 2010)
The Maré Museum, founded on 8 May 2006, arose from the desire of the inhabitants of the community to have a place of memory, a place that is immersed in the past and looks to the future, a place that reflects on this community, on their conditions and identities and on their territorial and cultural diversity. The intention of the Maré Museum is to break with the tradition that the experiences to be recollected and the places of memory to be remembered are those elected by the official version, the "winner" version of the story that restricts the representations of history and memory of large portions of the population. The Maré Museum, as a pioneer initiative in the city scene, proposed to expand the museological concept, so that it is not restricted to intellectual social groups and cultural spaces that are not accessible to the general population. The museum has established recognition that the slum is a place of memory and so has initiated a museographic reading of the Mare community. ..